Factores socio-económicos que influyen en la creación de nuevas empresas que generen oferta de empleos para la ciudad de Guaranda, en el periodo 2015-2016 - Vargas Angulo, Elvis Rafael (2017)
In the city of Guaranda in particular is characterized by own people enterprising, that reason to make this project of research focused in determine them factors partner-economic that influence to the time of the creation of companies, that generate offer of jobs, the At present it is important to conduct research in order to identify the types of businesses that are developed in the city of Guaranda, and subsequently to identify those factors that influence at the time of start with your company or business, which make it possible for future people wishing to undertake may have a vision of the characteristics that must be taken into account for the success of the business. There was used the methodology of exploratory investigation of field as the quantitative investigation realizing a statistical and numerical analysis, and the qualitative investigation realizing descriptions of the qualities and characteristics found in the trascurso of the investigation and the application of the used skills of investigation there were the surveys applied to the population of study of take care of Guaranda. The realized investigation has decided that the socio-economic factors that more influence the creation of new companies are: The most excellent social factor is the Motivation to tackle, that it is realized by the need, level of education, generation of employment, as for the Economic thing, there are the most common Financing routes they are those who gain access to a Bank loan, between others, There was a methodological analysis it was determined that the internal factors more central in the creation of new businesses in the city of Guaranda are: strategic location of the business, academic level professional experience in entrepreneurial activity.